Preservation of Traditional Sports of Geudeu-Geudeu Wrestling With Modification of Match Rules in the Pidie Jaya Community of Aceh - Safwan, Edi; Jamaliah, Naimatul; Zulfikri, Zulfikri (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
The growth of traditional sports begins with daily habits with various activities in the form of movements towards a game which contains elements of the art of sports and social values that exist throughout Indonesia. The aim of the study was to modify the rules of the traditional sport of geudeu-geudeu wrestling. The research method used is research and development (R & D) with the stages of the ADDIE method, namely: analyze, design, develop, implement, evaluate. The research instruments were questionnaires and interviews containing statements related to the modification of the traditional sport rules of geudeu-geudeu wrestling. The research subjects were geudeu-geudeu trainers and 10 youths in Pidie Jaya Regency. Data analysis by looking for the magnitude of the relative frequency or in the form of a percentage. The results of this study indicate that there are four alternative answers chosen by respondents, namely 62.23% strongly agree, 34.24% choose agree, and 3.53% disagree, with the modification of the geudeu-geudeu martial arts regulations. Youth 60.02% strongly agree, 36.55% agree, 3.43% disagree with the modification of the traditional sport rules of geudeu-geudeu wrestling. Geudeu-geudeu and youth coaches 60.12% strongly agreed, 35.39% agreed with the development of the traditional sport regulations of geudeu-geudeu wrestling, and 4.49% disagreed with the modification of the traditional sport rules of geudeu-geudeu wrestling.